2023
DOI: 10.1021/acs.macromol.2c02359
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Sulfonium Sulfonate Polymers: Impacts of Substituents and Inverted Dipole

Abstract: Research involving polymer zwitterions typically involves the preparation of ammonium-based structures and their study as coatings or gels that impart hydrophilicity and/or antifouling properties to substrates and materials. More recent synthetic advances have produced a significant expansion in polymer zwitterion chemistry, especially with respect to the composition of the cationic moieties that open new possibilities to examine polymer zwitterions as amphiphiles, functional surfactants, and components of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…[32] However, sulfobetaine may not be the optimal ZI type for a given electrolyte environment; within at least one popular ILE, other ZI chemistries (carboxybetaine, phosphorylcholine) yielded better performance enhancements. [7] Several additional ZI chemistries have been shown to be synthetically accessible (e. g. trimethylamine N-oxide, [6] sulfonium sulfonates, [33] fluorinated choline phosphates, [34] etc. ), yet most of these have not yet been examined for their potential use in battery electrolytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] However, sulfobetaine may not be the optimal ZI type for a given electrolyte environment; within at least one popular ILE, other ZI chemistries (carboxybetaine, phosphorylcholine) yielded better performance enhancements. [7] Several additional ZI chemistries have been shown to be synthetically accessible (e. g. trimethylamine N-oxide, [6] sulfonium sulfonates, [33] fluorinated choline phosphates, [34] etc. ), yet most of these have not yet been examined for their potential use in battery electrolytes.…”
Section: Discussionmentioning
confidence: 99%
“…Several additional ZI chemistries have been shown to be synthetically accessible ( e. g . trimethylamine N ‐oxide, [6] sulfonium sulfonates, [33] fluorinated choline phosphates, [34] etc. ), yet most of these have not yet been examined for their potential use in battery electrolytes.…”
Section: Discussionmentioning
confidence: 99%
“…Polymer zwitterions are characterized by their covalently linked cationic and anionic functionalities that give charge neutrality throughout the polymer chain. [ 71 ] Furthermore, zwitterion‐zwitterion pairing can occur between the oppositely charged groups of zwitterions in close proximity, giving rise to intra‐ and inter‐ molecular associations which can ultimately dictate physical properties of a system. However, the ionic nature of these associations makes them prone to dissociation in the presence of salt solutions which screen charge.…”
Section: Stimuli‐responsive Polymersmentioning
confidence: 99%
“…For example, Brown et al recently showed that reversing the dipole orientation from poly(sulfothetin styrene) to poly(sulfonium sulfonate styrene) led to higher stability against nucleophiles due to a reduction in inter-zwitterion interactions, which are shielded in the case of poly(sulfonium sulfonate styrene) by the n-butyl groups extending from the chains. [48]…”
Section: Zwitterionic Polymersmentioning
confidence: 99%